A review of the multidisciplinary approach to develop elite players at professional football academies: Applying science to a professional context - Raya-Castellano, P. E.; Uriondo, L. F. (International Journal of Performance Analysis in Sport, 2015)
This paper reviews literature related to several disciplines affecting performance in football at an academy level and clearly defines some roles of the staff working within professional football academies. This includes the lack of notational analysis research transferable to youth matches and the absence of research covering performance analysts' or coaches' behaviour during video analysis sessions; the practice activities used by coaches and their behaviour within practical sessions and how these influence the players' individual tactical capabilities; insights on how to approach fitness training depending on football's physical demands, the player's position, level of maturity and style of play; and psychological (individual and organisational) support to overcome intrinsic and extrinsic factors which impede the fulfilment of players' potential. It also provides head coaches, fitness coaches and psychologists working at professional football academies with some advice, based on scientific knowledge, to better carry out their responsibilities. Finally, it intends to raise the awareness of scientists and practitioners on the need to work together to understand the academy context and therefore approach practice more efficiently, which ultimately will contribute to developing professional knowledge.